Jews and Theater in an Intercultural Context: Jews and Theater in an Intercultural Context - Nahshon, Edna (Brill's Series in Jewish Studies, 2012)
A collection of essays by an international cadre of theater scholars, which addresses Jewish theater practitioners, playwrights, critics, financiers and audiences roles in the development of the European and American theater.